Hubungan Pola Asuh Orangtua Dengan Tingkat Ketergantungan Gadget Pada Anak Usia Prasekolah Di Kecamatan Sumber Kabupaten Probolinggo - Arfa Faisza Almaera Putri; Miftakhul Ulfa; Ervin Rufaindah (JUKEJ : Jurnal Kesehatan Jompa, 2023)
the level of gadget dependence on preshool-age children is influenced by parenting styles because parents have a role in exemplifying and influencing children in using their gadgets. To examine the correlation between parenting style and the use of gadgets in preschool-aged children in Sumber District, Probolinggo Regency. The research design uses cross-sectional with a sample of 54 respondents. The sampling technique used purposive sampling consisting of 49 respondents in PKK Kindergarten in Sumberanom Village and Sumber II Kindergarten, Sumber District, Probolinggo Regency. Parenting styles were measured using the Parenting Styles and Dimensions Questionnaire-Short Version (PSDQ) and the use of gadgets in early childhood was measured using the Smartphone Addiction Test with the sommers'd analysis test. The results showed that most parents adopted democratic parenting (61.2 % ) and most of the children were addicted to gadgets (72.4%). Sommers'd test showed that the value of p = 0.005 with a value of r = 0.311 (p <α = 0.05). It can be concluded that there is a moderate relationship between parenting styles and the use of gadgets in preschool- aged children . Keywords : Parenting, gadgets, preschool age children